Engineering Metal-Organic Frameworks (MOFs) for Efficient Photocatalysis - Deng, Xiaoyu; Hao, Mingming; Li, Zhaohui (Current Organic Chemistry, 2018)
Photocatalysis can transform solar energy into chemical energy and is a promising technology to ameliorate the current environmental pollution and energy shortage. Due to their unique structural characteristics, metal-organic frameworks (MOFs), a class of micro-mesoporous hybrid materials, are recently emerging as a new type of photocatalysts and have already been applied for a variety of photocatalytic reactions, including the most relevant for environmental concerns such as CO2 reduction, H2 evolution, the oxidation of various pollutants as well as light-induced organic transformations. Although a number of excellent reviews on MOF-based photocatalysis have already been published, the current short review focuses on different strategies to engineer the MOF-based photocatalysts, with an aim for efficient photocatalysis. The review summarized different strategies to enhance the light absorption of the MOFs and improve the photogenerated charge separation, which is considered to be important factors in influencing the performance of the photocatalysts. As a unique advantage of using MOFs as photocatalysts, the implementing of other catalytic active sites into a single MOF material to enable the MOFs to behave as a multifunctional catalyst for light-induced tandem/cascade reactions was also introduced in this review. Finally, personal opinions on the opportunities and challenges facing the MOFs-based photocatalysis and its developing trend were also addressed. We hope that this review can provide some guidance for a rational development of highly efficient MOFs-based photocatalysts and serve as a starting point to design more MOF-based multifunctional catalysts via a successful coupling of MOF-based photocatalysis with molecular catalysis/metal catalysis/organocatalysis since we believed that it is the trend of the MOF-based photocatalysis.
Keywords: photocatalysis